Ecological aspects of the floral phenology of the cork-oak (Q suber L): why do annual and biennial biotypes appear? - Elena-Rossello, J. A.; de Rio, J. M.; Valdecantos Garcia, J. L.; Santamaria, I. G. (Ann. For. Sci., 1993)
Phenological observations (periods of flowering and pollination, floral structures, etc) were made over a 3-year period in natural populations of Q suber. We demonstrated the existence of 2 different types of seed cycles in the cork-oak. The 'annual biotype', requires only 1 season to complete its reproductive cycle (ie, similar to that of the Lepidobalanus group), whereas the 'biennial biotype' requires 2 full years (similar to Erythrobalanus). The variability observed in the cork-oak, during the reproductive cycle, and the meaning of the existence of 2 different reproductive strategies in the same species, are discussed
Keywords: annual and biennial biotypes; cork-oak; ecological variability; floral phenology; Quercus; reproductive strategies

Evidence for hybridization between sympatric holm-oak and cork-oak in Spain based on diagnostic enzyme markers - Elena-Rossello, J. A.; Lumaret, R.; Cabrera, E.; Michaud, H. (Plant Ecology, 1992)
Hybridization has been detected in mixed populations of juvenile cork-oak and holm-oak individuals using three diagnostic enzyme loci coding for esterases, leucine amino peptidases and acid phosphatases respectively. Among the 35 studied individuals, 29, 5 and 1 were identified as holm-oak, cork-oak and hybrid respectively. Such diagnostic markers are likely to be useful to detect and remove hybrids at the juvenile stage in areas where the holm-oak is grown for acorn production and the cork-oak is cultivated for cork. This is necessary since hybrid adults produce neither cork nor acorns of high quality.
Keywords: cork-oak; enzyme markers; holm-oak; Hybridization; Quercus